Relations between indoor rehabilitation and basic health services in a developing country - Taslim Uddin; Badrunnessa Ahmed; Farzana Khan Shoma (Frontiers Media S.A., 2023)
Backgroundand Introduction: Physical rehabilitation is vital for patients to regain maximum function. Approximately 80% of people with a disability live in developing countries, where they face multiple challenges in rehabilitation. The goal of the study was to conduct an analysis of indoor rehabilitation programs based on the demographics and medical conditions of the admitted patients and to relate to the available basic health and rehabilitation facilities.MethodsThis was a mixed method study conducted in an inpatient rehabilitation ward of a tertiary level academic university hospital in a developing country. All admitted patients who stayed for a period of minimum two weeks were included in the study. Demographic and clinical data were obtained by means of a retrospective medical record review utilizing a standardized data extraction form. The study was further strengthened by an online literature search for the available documents for analysis, relation, and discussion.ResultsAmong the 1,309 admitted patients was male- female ratio was 10:7, with the majority (31.4%) cases falling between the ages of 46 and 60yrs. Rehabilitation outpatient department was the principal mode of admission (78%), and musculoskeletal and neurological conditions represented the maximum number (79.8%). Majority of patients (60.8%) were discharged home on completion of the rehabilitation program with a large number of patients who were absconded. Poor health budget allocation and lack of prioritization of the rehabilitation sector face multiple challenges, including the rehabilitation team functioning resources, space crisis for expansion which was further impacted by the COVID-19 pandemic.ConclusionsThe country's current health-related rehabilitation process and socio-demographic variables have a negative relationship. There was a large number of missing data in the medical records and many patients were lost prematurely from the indoor rehabilitation program. Musculoskeletal disorders were common, and the majority of patients were discharged home once the program was completed.